2012
DOI: 10.1007/s12070-011-0464-7
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Double Blind Comparative Study Comparing Efficacy of Granisetron and Ondansetron for the Prophylactic Control of Postoperative Nausea and Vomiting in Patients Undergoing Middle Ear Surgery

Abstract: The objective is to evaluate the prophylactic profile, efficacy of granisetron and ondansetron to prevent postoperative nausea and vomiting (PONV) after middle ear surgery. In a randomized, double blind trial, one hundred patients undergoing middle ear surgery received either granisetron 1 mg or ondansetron 8 mg in equal volume (n = 50 for each) intravenously towards the end of surgery and before reversal of anaesthesia. A standard general anaesthetic technique was employed. Postoperatively, during the first 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In a meta-analysis by Shen et al dexamethasone and ondansetron have been found to be more effective at reduction of PONV in comparison to ondansetron after strabismus surgery [ 23 ]. As granisetron is more efficacious than ondansetron in prevention of PONV [ 24 , 25 ], it is possible that dexamethasone cannot further enhance the efficacy of granisetron in strabismus surgery as seen in our study. Again, efficacy of any drug in preventing an undesirable response also depends upon the baseline risks of the patients.…”
Section: Discussionmentioning
confidence: 84%
“…In a meta-analysis by Shen et al dexamethasone and ondansetron have been found to be more effective at reduction of PONV in comparison to ondansetron after strabismus surgery [ 23 ]. As granisetron is more efficacious than ondansetron in prevention of PONV [ 24 , 25 ], it is possible that dexamethasone cannot further enhance the efficacy of granisetron in strabismus surgery as seen in our study. Again, efficacy of any drug in preventing an undesirable response also depends upon the baseline risks of the patients.…”
Section: Discussionmentioning
confidence: 84%
“…This given property can be utilized for prevention of PONV where longer duration prophylaxis is required as in cases of middle ear surgeries. Granisetron with half life of eight to nine hours is also effective in preventing PONV by causing irreversible blockade of 5HT3 receptor on vagal 11,12 afferents from gut .…”
Section: Discussionmentioning
confidence: 99%